Importance of the sugarcane industry in the formal employment in the state of Mato Grosso do Sul during the period of 2008 to 2014 - Defante,Lilliane Renata (2020)
Abstract: In the early 2000s, sugarcane experienced high growth in Brazil and Mato Grosso do Sul experienced the highest growth, with a 398%% increase. We analysed the impact of the sugarcane industry on formal employment and wages in Mato Grosso do Sul between 2008 and 2014. We used a Normalized Concentration Index (nCI) decomposed into Location Quotient (LQ), modified Hirschman Herfindahl Index (HHm), and Relative Participation (RP). Data were collected in the Annual Report on Social Information (RAIS). The nCI allows a general perception of concentration since LQ and HHm give greater weight to small municipalities with few activities, and the RP underestimates the importance of industry for these same municipalities. Thus, the municipality of Dourados, the second largest in the state, had an RP of 9%, but low LQ and HHm. The sugarcane industry plays an essential role in the economy of small towns, where it generates most of the formal jobs, with higher salaries. However, the impact is concentrated in a few small cities. Another effect is the fast disappearance of the benefits of the sugarcane industry in areas where processing units were closed. The dependence of the sugarcane industry in small municipalities is a concern whose solution should be further studied.